2022
DOI: 10.1248/cpb.c21-00794
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis of 4,4-Disubstituted 3,4-Dihydropyrimidin-2(1<i>H</i>)-ones and -thiones, the Corresponding Products of Biginelli Reaction Using Ketone, and Their Antiproliferative Effect on HL-60 Cells

Abstract: An efficient synthetic method for novel 4,4-disubstituted 3,4-dihydropyrimidin-2(1H)-ones 5 and -thiones 6 was developed. The cyclocondensation reaction of O-methylisourea hemisulfate salt 11 with 8 gives a tautomeric mixture of dihydropyrimidines 12 and 13 following acidic hydrolysis of the cyclized products to produce 5 in high yields. Thionation reaction of 5 at the 2-position smoothly proceeds to give 2-thioxo derivatives 6. These compounds 5 and 6, corresponding to the products of a Biginelli-type reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…The structure of DP01-DP11 is introduced 6-methyl or phenyl group on 2-methythio DP, on the other hand, that of P12-DP19 is 6-oxo one. Our previous studies demonstrated that 2-oxo DPs do not induce cytotoxic effects against HL-60 cells [18,20]. Therefore, all these ndings suggest that the introduction of the oxo-group into the structure of DP results in the reduction of cytotoxicity against NB4 and HL-60 cells.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The structure of DP01-DP11 is introduced 6-methyl or phenyl group on 2-methythio DP, on the other hand, that of P12-DP19 is 6-oxo one. Our previous studies demonstrated that 2-oxo DPs do not induce cytotoxic effects against HL-60 cells [18,20]. Therefore, all these ndings suggest that the introduction of the oxo-group into the structure of DP results in the reduction of cytotoxicity against NB4 and HL-60 cells.…”
Section: Discussionmentioning
confidence: 77%
“…Cytotoxicity of 2-methylthio DPs against NB4 or HL-60 cells was measured by XTT assay as described previously [20] or WST-8 assay kit according to the manufacturer's instructions. Brie y, XTT/PMS mixed solution (1.5 mM XTT and 0.025 mM PMS in PBS) or WST-8 solution of a quarter or a tenth of the medium in well was added followed by incubation at 37 °C for 4 h or 1 h. Next, the plate was mixed on a mechanical plate shaker, and absorbance at 450 nm was measured with a microplate reader, SpectraMax Pro M5 e (Molecular Devices, USA).…”
Section: Cell Viability Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The process makes use of 2-aminobenzothiazole 152 as a nitrogen source, dimedone 33, and aromatic aldehydes 2 (Scheme 76) [156]. Unlike aldehydes, ketones are not reactive enough to engage in the classical Biginelli reaction acting as electrophiles and they always react as a nucleophile via enolization; however, very recently, Nishimura et al prepared the key intermediate 171 by using TiCl4 and pyridine in a Knoevenagel-type condensation (Scheme 77) [157]. Thus, the cyclocondensation reaction of this compound 171 with O-methylisourea hemisulfate salt 5 gave a tautomeric mixture of dihydropyrimidines 172 and 173; this mixture was hydrolyzed to produce 4,4-disubstituted 3,4-dihydropyrimidin-2(1H)-ones 174 in high yields; these products had been inaccessible and hitherto unavailable for medicinal chemistry and were assessed for their antiproliferative effect on a human promyelocytic leukemia cell line, HL-60.…”
Section: Modification Of Two Componentsmentioning
confidence: 99%
“…and pyridine in a Knoevenagel-type condensation (Scheme 77) [157]. Thus, the cyclocondensation reaction of this compound 171 with O-methylisourea hemisulfate salt 5 gave a tautomeric mixture of dihydropyrimidines 172 and 173; this mixture was hydrolyzed to produce 4,4-disubstituted 3,4-dihydropyrimidin-2(1H)-ones 174 in high yields; these products had been inaccessible and hitherto unavailable for medicinal chemistry and were assessed for their antiproliferative effect on a human promyelocytic leukemia cell line, HL-60.…”
Section: Modification Of Two Componentsmentioning
confidence: 99%